Taṭbīq Ṭarīqah Retelling Story Bi ar-Rusūm al-Mutasalsilah Li Tarqiyah Qudrah aṭ-Ṭalabah `Alā Mahārah al-Kalām (Dirāsah Tajrībiyah Bi Bāb an-Najāḥ Banda Aceh) - Buhori Muslim; Nurdiyani Nurdiyani (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
In the second language, speaking is a basic skill in learning language, because language it selft is speech, a person not considered of mastering the language except by mastering the speaking. The students of Babun Najah not only found difficult in speaking Arabic language but got borred as well. Thus, student had a very low ability. It was caused by the disagreement between method used by teacher and do not use the interesting media according to students’ condition, it makes the students felt bored, lack of attention to the subject; even some of them spoke during the teaching and learning process. So the learning process runs ineffectively. This resulted in the limit ability of students to speak Arabic. Based on this problem that has been studied by the researchers, so we need for solution to overcome these problems, including: applying the Retelling Story method with the serial images in teaching Arabic language to reach the purposes of teaching speaking skills, in hopes of increasing student ability in speaking skills by combining these two variables. The purposed of this research is to know students’ responses to speaking skills and students’ abilities in speaking Arabic language using the retelling method and serial pictures in Babun Najah Banda Aceh boarding school. Quantitative supported by qualitative approach along with experimental method was used by the researcher. Purposive sampling was used to find the second graders of II-C as a control class and II-D as an experimental class that was consisted of 23 students. The results are that students’ response toward Retelling story Method with the pictures series is well, and the use of Retelling story Method with the pictures series was effective and it gave a good impact on students of Babun Najah Banda Aceh boarding school, which the result from the t-test relate calculation is greater than t-table result, that is 1,69 < 1,93.